1978
DOI: 10.1007/bf03161000
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol, a dopaminergic antagonist: Somatostatin-like inhibition of glucagon and insulin release from the isolated, perfused canine pancreas

Abstract: Summary. The effect of haloperidol, a dopaminergic antagonist, on insulin and glucagon secretion was investigated using the isolated, perfused canine pancreas. Haloperidol at 4 x 10 .7 to 10 .5 mol/1 caused a dose-dependent inhibition of glucagon release both at low (25 mg/100 ml) and high glucose concentrations (150 mg/100 ml). At the low glucose concentration insulin release was already maximally suppressed. At the high glucose concentration haloperidol (4 × 10 -7 to 10 .5 mol/1) also caused a dosedependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

1980
1980
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…For example, sulpiride alters glucose homeostasis in rats (Baptista, 1999), but our studies indicate it has little inhibitory effect on K ATP channels, even at high concentration. Third, studies have shown that haloperidol can either reduce insulin secretion (Hermansen, 1978) or have no effect (ElDenshary et al, 1982), but an increase in secretion (which is expected if the drug blocks K ATP channels) has not been reported. It is possible that haloperidol blocks Ca 2 þ currents in b cells, as it does in other tissues, which leads to a reduction in insulin secretion, glucose intolerance, and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sulpiride alters glucose homeostasis in rats (Baptista, 1999), but our studies indicate it has little inhibitory effect on K ATP channels, even at high concentration. Third, studies have shown that haloperidol can either reduce insulin secretion (Hermansen, 1978) or have no effect (ElDenshary et al, 1982), but an increase in secretion (which is expected if the drug blocks K ATP channels) has not been reported. It is possible that haloperidol blocks Ca 2 þ currents in b cells, as it does in other tissues, which leads to a reduction in insulin secretion, glucose intolerance, and diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine blockade by metoclopramide may directly influence metabolism or act through changes in secretion of other hormones. Studies using specific agonists and antagonists have suggested actions of dopamine to both increase and decrease insulin and glucagon secretion (Hermansen, 1978;Samols & Stagner, 1979) but circulating peripheral insulin and glucagon levels were unaltered by metoclopramide in our experiments. Metoclopramide has been reported to increase or produce no change in growth hormone secretion in man and the rat (Cohen et al, 1979;Fang et al, 1977) and no metoclopramide-induced change in circulating growth hormone concentrations occurred in the present study.…”
Section: Discussionmentioning
confidence: 43%
“…Although the studies about the effect of halopeidol on blood glucose metabolism is less than that of chlorpromazine, there are studies that show haloperidol infusion into the canine pancreas inhibited insulin secretion (Hermansen, 1978;Lechin, 1981). Brambilla et al (1976) suggested that haloperidol reduced peripheral glucose metabolism in a study of 18 schizophrenic patients treated with haloperidol 6 mg i.m.…”
Section: Discussionmentioning
confidence: 98%
“…Besides chlorpromazine, haloperidol also inhibited the secretion of insulin in the canine pancreas (Hermansen, 1978;Lechin, 1981) and there is a report that sulpiride decreased glucose tolerance in the dog and the human (Lechin et al, 1979). Two case reports show that olanzapine induced hyperglycemia and diabetes (Wirshing et al, 1998), along with a case report that quetiapine also induced diabetes (Maxwell et al, 1990).…”
Section: Introductionmentioning
confidence: 92%